Implementasi Kebijakan Penataan Toko Modern Minimarket di Kota Semarang - Diah Anggraeni Novitasari; Sundarso Sundarso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Implementation of modern minimarket store structuring policy in Semarang City is one of the efforts made by the government in confronting the proliferation of establishments minimarket. Implementor of this policy is the Integrated Licensing Service Agency of Semarang and the Department of Industry and Trade of Semarang. The purpose of this research is to describe and analyze how the implementation of modern minimarket store structuring policy and to describe and analyze what are the factors that drive and impede the modern minimarket store structuring policy. Effectiveness of policy implementation process seen from five factors: appropriateness of the policy, the accuracy of the executor, the target accuracy, precision and accuracy of the support environment. Key factors driving and inhibiting the use of the theory of George C. Edwards III, communication, resources, disposition and bureaucratic structure. This research used a qualitative approach with descriptive type, which aims to illustrate how the process of policy implementation arrangement modern shops conducted in depth by looking at the facts that exist. Analysis techniques to acquire data through observation, interviews and document research. Drawing conclusions through interactive analysis belongs to Miles and Huberman to perform data reduction and data presentation. The results of research that is modern minimarket store planning policy in the city of Semarang has been running well, but there are still some things that have not been in accordance with existing regulations. Inhibiting factors of this policy is the lack of budget, facilities and infrastructure.